Reference broadcast synchronization and time division multiple access implementation on WSN - Sabriansyah Rizqika Akbar; Mochammad Hannats Hanafi Ichsan; Aulia Arif Darmawan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Various kinds of technology have been developed to assist obtain information. One of them is a Wireless Sensor Network (WSN). WSN is a wireless network consisting of multiple nodes connected wirelessly. WSN nodes on a device have small resources in the form of batteries. The main problem which owned by WSN was in the data collection process possible collisions data, there are nodes that transmit data at the same time. Time Division Multiple Access (TDMA) was able to provide data on the delivery schedule of each node. So no nodes that transmit data at the same time. But in order to apply the system each node should have equal time. One method that able to provide equalization time was Reference Broadcast Synchronization (RBS). This method synchronizes multiple nodes that have different local time (on the receiver) with the help of node that provides synchronization marks (beacons). Hence this each node was able to transmit data in accordance with the TDMA method that has been implemented. In addition time synchronization performed using RBS give equal time with accuracy up to microseconds. That case certainly makes the WSN node able to provide accurate information to guarantee the absence of errors due to data collisions. This research succesfully sending data delivery schedule by time slots that provided by RBS and time synchronization by TDMA average time delay 2285.9 microseconds.